Home energy monitoring system using wireless mesh network - Wijaya, Kelvin. (2010)
In the past few years, there have been a lot of interests in combining Power Line and Wireless Communication technologies for Home energy monitoring and Home automation/control systems. The combination of these technologies gives a wider and better coverage of services to the user. With the increasing number of internet usage and advanced development in networking areas, remote energy monitoring has been made possible. For project wise, Ethernet-driven and Wireless-Zigbee energy monitoring devices are being used. Based on the US consumer electronic market, ZigBee/802.15.4 has been the winning application of wireless networking solutions for Smart energy and Automatic Meter Reading (ARM).